Communicating Science through Art. Victorias Cells Project (Global Journal of Medical Research, 2023)
Victoria s cells project was created from the idea of easier training of healthcare personnel and facing theoretical and practical aspects of improving communication This innovative method allows one to associate benign and malignant cellular images and or patterns characterized by a wide range of shapes and color shades evoking animals common objects and colorful aquariums with features easily memorized by analogy under the microscope The project implies different sections subclassified using different iconography able to draw the viewer s interest and easily memorize the cytological interpretations and describe practical interventions to promote effective communication in cancer screening with different new and interactive information tools